2021
DOI: 10.7759/cureus.19574
|View full text |Cite
|
Sign up to set email alerts
|

Homonymous Hemianopsia Due to the Infarction in the Splenium of the Corpus Callosum

Abstract: The precise functions of the splenium of the corpus callosum (CC) remain unclear, and infarction of this location manifests varied clinical symptoms. We describe a rare case of right homonymous hemianopsia resulting from pure infarction in the right-side splenium of the CC. An 85-year-old man presented with right homonymous hemianopsia lasting for a week. Diffusion-weighted imaging showed a high-intensity area in the right-side splenium of the CC and did not show any other lesions in other portions of the visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Within those cases, no case had been reported with homonymous hemianopsia before, while four of them had metamorphopsia. 17 In this current case report, metamorphopsia came to the forefront as a visual symptom.…”
Section: Discussionmentioning
confidence: 66%
“…Within those cases, no case had been reported with homonymous hemianopsia before, while four of them had metamorphopsia. 17 In this current case report, metamorphopsia came to the forefront as a visual symptom.…”
Section: Discussionmentioning
confidence: 66%
“…The structure of CC can be divided into four classical parts in the order from front to back: rostrum, genu, body and splenium ( 54 ). Consistent with previous reports ( 5 ), we found that the incidence of ‘pure’ CC infarction was rare, while the mental disturbance and cognitive dysfunction were more prominent than ‘complex’ CC infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we reported for the first time that acute infarction in the splenium had a higher tendency of cognitive decline than that in the genu. As the most vulnerable area of the CC infarction, the splenium is more vulnerable to insufficient blood supply, and the splenium lesions were known to be related with cognitive disorder, aphasia, homonymous hemianopsia, alien hand syndrome and so on ( 54 ). Therefore, we believe that the splenium plays an important role in the high incidence of SCD caused by CC infarction to some extent.…”
Section: Discussionmentioning
confidence: 99%